2022
DOI: 10.15249/16-1-285
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on business ethics in South African small and medium enterprises

Abstract: SMEs are the driving force of economies. However, they face challenges that affect their long-term survival, such as developing ethical business environments. Business ethicsrelated research is underdeveloped in SMEs, thus limiting our understanding of business ethics in SMEs. The purpose of this qualitative study was to investigate how business ethics is conceptualised in SMEs, using the Delphi Technique. In SMEs, business ethics is viewed as doing the right thing, having integrity, being transparent, trustw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…South Africa's entrepreneurship landscape has been labelled laggard relative to other less developed African countries because of its inconsistent performance and low estimated established firm measures (Swartz, Amatucci & Marks 2019). Amongst many challenges contributing to low entrepreneurial activity, entrepreneurs have to deal with ethical challenges (Robinson & Jonker 2017;Van Wyk & Venter 2022). Van Der Walt, Jonck and Sobayeni (2016) indicated a decline in ethical behaviour in the South African business environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…South Africa's entrepreneurship landscape has been labelled laggard relative to other less developed African countries because of its inconsistent performance and low estimated established firm measures (Swartz, Amatucci & Marks 2019). Amongst many challenges contributing to low entrepreneurial activity, entrepreneurs have to deal with ethical challenges (Robinson & Jonker 2017;Van Wyk & Venter 2022). Van Der Walt, Jonck and Sobayeni (2016) indicated a decline in ethical behaviour in the South African business environment.…”
Section: Introductionmentioning
confidence: 99%
“…Mai, Zhang & Wang 2019). Despite the increasing focus on ethics, Van Wyk and Venter (2022) argued that business ethics research is still lacking in small enterprises. Mpinganjira et al (2016) found that the South African corporate sector has mechanisms to enhance its ethical code of conduct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small medium and micro enterprises (SMEs) play a significant role in the development of a country (Bayati, 2007;van Wyk and Venter, 2022). In South Africa, more than 98 percent of business entities are SMEs and they contribute up to 57 per cent of the gross domestic product, employ between 50 and 60 percent of the country's work force across all sectors, and are responsible for a quarter of job growth in the private sector (Kalidas et al, 2020;Robson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, more than 98 percent of business entities are SMEs and they contribute up to 57 per cent of the gross domestic product, employ between 50 and 60 percent of the country's work force across all sectors, and are responsible for a quarter of job growth in the private sector (Kalidas et al, 2020;Robson et al, 2013). As such, they have become a key component in strategies for economic growth, job creation and poverty reduction (Agupusi, 2007;Botha et al, 2021;van Wyk and Venter, 2022). It is therefore beneficial for SMEs to strive to become high performance organisations (HPOs) as this leads to an increase in their growth and development, and their ability to contribute (even) more to the development of the country (Su, 2015).…”
Section: Introductionmentioning
confidence: 99%